Traffic Crime Law Enforcement On Over Dimensions - Yunanto Dwi Handoko; Maryanto Maryanto (Universitas Islam Sultan Agung, 2021)
The purpose of this study describes how the law enforcement of Act No. 22 of 2009 concerning Road Traffic and Transportation against over-dimensions as well as obstacles and solutions in overcoming public transportation law enforcement that is Over-Dimensional. The approach method used in this research is empirical juridical. Based on the research, it can be concluded that law enforcement in over-dimensional cases is contained in the provisions for the mandatory testing of types of public transportation vehicles or over-dimensional vehicles regulated in Act No. 22 of 2009 concerning Road Traffic and Transportation. In addition to Act No. 22 of 2009 concerning Road Traffic and Transportation, there is also Government Regulation Number 55 of 2012. Over-dimensional vehicles are strictly prohibited because in the event of a traffic accident, the fatality of the victim is very high. The over-dimension does not take into account the factors of security, safety and order and the smoothness of traffic, and only cares about the profits of public transport entrepreneurs, so they must be punished in accordance with the applicable laws and regulations.